Detection of leptospiral antibodies and DNA in freshwater fish - Brandt, LaRoy; Willems, Emily; Morgan, Joey; Wisnieski, Lauren; Boukobza, Sloane; Geer, Allison; Duke, Conner; Brovarney, Scott; Noah, Brooke; Coarsey, Michele D.; Naikare, Hemant; Verma, Shashi S.; et al. (Frontiers in Veterinary Science, 2025)
Leptospirosis is an important zoonotic disease that is maintained in populations due to chronic kidney infection of reservoir mammals. Previous work from our lab has identified rodents, voles, shrews, chipmunks and several species of amphibians and reptiles as hosts of Leptospira spp. in the Cumberland Gap Region of Kentucky, Tennessee, and Virginia. The aim of this study was to determine if fish contribute to the maintenance of the pathogen in the aquatic environment. Fish (n = 238), belonging to 19 genera, were collected from seven different locations in the Powell River in East Tennessee. Fish kidneys were harvested and screened for leptospiral DNA using a TaqMan quantitative polymerase chain reaction (qPCR) assay that targets pathogenic Leptospira spp. Blood samples were collected for measuring leptospiral antibodies using microscopic agglutination test (MAT). Of the 238 fish screened, 11 were positive by either qPCR or MAT (4.62%; 95% CI: 2.33–8.12). Of these 3 (3/238; 1.26%; 95% CI: 0.26–3.64) were positive by qPCR and 8 (8/237; 3.38%; 95% CI: 1.47–6.54) were found to have antibodies to at least one leptospiral serovar by MAT. This is the first report of leptospiral DNA detection in fish kidneys, providing insights on the potential role of fish in the epidemiology of leptospirosis in the region.